Evaluasi Potensi Fisik Siswa Sebagai Hasil Belajar Pendidikan Jasmani, Olahraga dan Kesehatan (Studi pada SMP Sederajat di Kabupaten Jember) - ardi bernis wiranata (Journal of Sport Science and Education, 2018)
This study was conducted to measure the students achievement in evaluation learning outcomes ofphysical education. There are five research questions that will be analyzed: (1) how did the teacherunderstand the learning objectives?, (2) how did the teacher make the learning objectives as the targetof evaluation?, (3) how did the teachers evaluation has been linked with learning objec tives?, (4)how did the objectives which designed by the teacher has been effective to improve the studentsphysical potential?, (5) how did the learning objectives have been achieved?. This study useddescriptive qualitative method. The data were collected by using the model of evaluation CIPP(context, input, process, and product). The reasearcher did the observation in Junior high school ofdistric Jember and chose all students of class VIII which consist of 1210 students. The result of thestudy revealed that: (1) the teacher did not understand the objectives of learning physical educationyet, (2) the teacher did not make the learning objectives as a target of evaluation, (3) the teachersevaluation did not linked with learning objectives, (4) the learning objectives designed by the teacherdid not effective to improve the students potential physic, (5) the learning objectives did notachieving the students achievement. Based on the explanation above, it is concluded that vitalitycondition was 57.38% (healthy student) and 42.62% (unhealthy student).